2012
DOI: 10.1186/1556-276x-7-617
|View full text |Cite
|
Sign up to set email alerts
|

InGaN/GaN multilayer quantum dots yellow-green light-emitting diode with optimized GaN barriers

Abstract: InGaN/GaN multilayer quantum dot (QD) structure is a potential type of active regions for yellow-green light-emitting diodes (LEDs). The surface morphologies and crystalline quality of GaN barriers are critical to the uniformity of InGaN QD layers. While GaN barriers were grown in multi-QD layers, we used improved growth parameters by increasing the growth temperature and switching the carrier gas from N2 to H2 in the metal organic vapor phase epitaxy. As a result, a 10-layer InGaN/GaN QD LED is demonstrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…In the last 2 decades, growth techniques of InGaN QDs, i.e., metalorganic chemical vapor deposition (MOCVD) and molecular-beam epitaxy (MBE), are extensively studied and well developed. By using these methods, InGaN QD LEDs and LDs, which emit from green to red, have recently been demonstrated with superior performance over equivalent QW-based counterparts [ 13 - 17 ]. However, only few optical investigations on the carrier transport and relaxation in InGaN QDs have been made to further understand the carrier recombination processes [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 decades, growth techniques of InGaN QDs, i.e., metalorganic chemical vapor deposition (MOCVD) and molecular-beam epitaxy (MBE), are extensively studied and well developed. By using these methods, InGaN QD LEDs and LDs, which emit from green to red, have recently been demonstrated with superior performance over equivalent QW-based counterparts [ 13 - 17 ]. However, only few optical investigations on the carrier transport and relaxation in InGaN QDs have been made to further understand the carrier recombination processes [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oliver et al reported the realization of micro-disk InGaN laser on sapphire substrates via growth interruption method [21]. Other research groups also employ the similar growth interruption methods to improve the optical properties of light emitting devices [22][23][24][25]. In this work, we investigated the effect of different growth interruption time on the surface morphology and optical properties of InGaN QDs grown on 2-inch silicon substrates.…”
Section: Introductionmentioning
confidence: 98%
“…Elevating the growth temperature of GaN quantum barrier (QB) is found to be an effective way to improve the quality of active region [13]. Although the growth temperature of QB is usually 50-150 higher than that of QW, it is still [14,15], growth interruption [16,17] and indium treatment [18][19][20]. Recently, Ren et al demonstrated that full hydrogen treatment after GaN barrier layer growth can enhance both indium incorporation and quantum efficiency [21].…”
Section: Introductionmentioning
confidence: 99%